2014
DOI: 10.1021/ja505556s
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Methyl Ammonium Lead Halide Perovskites: Implications for Photovoltaic Applications

Abstract: Hybrid organic/lead halide perovskites are promising materials for solar cell fabrication, resulting in efficiencies up to 18%. The most commonly studied perovskites are CH3NH3PbI3 and CH3NH3PbI3-xClx where x is small. Importantly, in the latter system, the presence of chloride ion source in the starting solutions used for the perovskite deposition results in a strong increase in the overall charge diffusion length. In this work we investigate the crystallization parameters relevant to fabrication of perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
412
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(443 citation statements)
references
References 36 publications
25
412
0
6
Order By: Relevance
“…Furthermore, as discussed earlier, UVO treatment to FTO substrates may also help reduce interface recombination. Cl in precursors has also been found to improve perovskite film quality such as coverage 40,41 . However, we did not observe significant difference on film coverage for CH 3 NH 3 PbI 3 and CH 3 NH 3 PbI 3-x Cl x films in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as discussed earlier, UVO treatment to FTO substrates may also help reduce interface recombination. Cl in precursors has also been found to improve perovskite film quality such as coverage 40,41 . However, we did not observe significant difference on film coverage for CH 3 NH 3 PbI 3 and CH 3 NH 3 PbI 3-x Cl x films in our study.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] The performance of this organic-inorganic halide cell is related to the optoelectronic properties of the organic lead halide absorber layer, most commonly CH 3 NH 3 PbX 3 (X = I and Br), and can be influenced by chemical composition, film morphology and device architecture. 7,[13][14][15][16][17] Recent reports have shown that using chloride containing salts or precursors (methylammonium chloride, MACl, and/or PbCl 2 ) can assist perovskite crystal growth because chloride ions or the formation of PbCl 2 nanocrystals (in a one-step deposition) can act as a nucleation center 11,18 due to size of Cl and PbCl 2 solubility. Additionally, the presence of MACl can also enhance the adsorption of lead iodide perovskite absorber on the TiO 2 substrate and produce large oriented crystallite domains by allowing slow crystal growth.…”
mentioning
confidence: 99%
“…By increasing the power of the vibration from 5 to 10 W, the morphology of thin film changes from irregular and small grains to grid-style large grain structures; thus, the SVPT is most effective at 5 W applied for 1 min. It is deduced that, as a result of the excitation by the ultrasonic vibration, the growth of large planar or 2D grains is suppressed due to an increase in the nucleation rate and the density of primary stable embryos [45][46][47]. In other words, in a dense population of stable seeds, the grain fronts will be confined by the neighboring cells.…”
Section: Resultsmentioning
confidence: 99%
“…This results in uniform mixing and distribution of the embryos generated on the substrate surface and within the film. This uniform and accelerated nucleation favors the size distribution, compactness, dimensionality, and the morphology of the crystallites [1,46,47]. grain fronts will be confined by the neighboring cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation